Percepções dos professores de apoio educacional especializado sobre a inclusão de alunos com o transtorno espectro do autismo - Silva, Amós de Souza (2018)
The inclusion of people with special needs at school still has many obstacles to consolidate. Autistic Spectrum Disorder (ASD) starts from the uterine life and continues to manifest after birth, characterized by motor deficits, communication and socialization. Including and enrolling students with ASD has been a major challenge for education. This study aimed to: understand the perceptions of Specialized Educational Support Teachers (PAEE) about the inclusion of students diagnosed with ASD; identify the difficulties and facilities presented by the students in the school environment; to know the teaching strategies used and to register the difficulties encountered by the teachers for the inclusion of students with ASD in the Regional Nucleus of Education (NRE) of Foz do Iguaçu / PR. This NRE covers nine municipalities in the Western Region of Paraná: Foz do Iguaçu, Itaipulândia, Matelândia, Medianeira, Missal, Ramilândia, Santa Terezinha de Itaipu, São Miguel do Iguaçu and Serranópolis do Iguaçu, with a total of 76 colleges. six, the research was carried out. Obtained authorization from the State Department of Education of Paraná and approval of the Ethics Committee on Human Research (CEP) of UNIOESTE. The qualitative approach was used, with interviews taking place in the second half of 2006 and the first half of 2017, after data collection with the Special Education Team of the NRE of Foz do Iguaçu on which colleges had students diagnosed with ASD in 2016, name of the accompanying teacher and the contact of the college. The incidence was seven students diagnosed with ASD in NRE and due to a refusal, six PAEEs formed the sample. Telephone contact with the teacher was made to schedule the interview, which took place in a reserved place, with an average duration of 30 minutes. For the interview a semi-structured questionnaire was used with open questions. The data obtained in the interviews were analyzed using the Collective Subject Discourse (DSC) technique. DSCs have shown that there are many difficulties for inclusion, such as insufficient training, lack of law enforcement and lack of structure. The difficulties of the students pointed out, as well as the strategies used, are related to the behavioral and pedagogical areas. Therefore, it is necessary to use measures that minimize the difficulties for the occurrence of inclusion, such as compliance with the law, improvement of training and encouragement of family participation.